Museums and cultural sustainability: stakeholders, forces, and cultural policies - Stylianou-Lambert, Theopisti; Boukas, Nikolaos; Christodoulou-Yerali, Marina (My University, 2014)
This paper explores the relationship between museums, cultural sustainability, and cultural policies. Specifically, it offers a theoretical model for the sustainable development of museums and a process for designing appropriate cultural policies for museums with cultural sustainability in mind. The case of Cyprus is used to demonstrate how strengths and gaps in cultural sustainability can be identified within a broader museum environment. The study examines the main stakeholders (the state, municipalities/ communities, and individuals), types of museums (archaeological, art, ethnographic, etc.) they establish and the forces influencing their decisions (such as politics, a sense of national identity, cultural tourism, economic revitalization, and personal agendas) in order to map the Cypriot museum environment and identify the emphasis placed on different parameters of cultural sustainability. By identifying cultural sustainability strengths and gaps on a national level, it becomes easier for cultural policy-makers to design appropriate cultural policies for museums.
Keywords: Cultural policy; Cultural sustainability; Cyprus; Museums; Theoretical model